2018
DOI: 10.1590/1980-57642018dn12-040004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and education on the processing of clustering and switching in verbal fluency tasks

Abstract: Verbal fluency (VF) is a widely used tool in neuropsychological assessment.Objective:We aimed to investigate the influence of age and educational level on clustering and switching in three VF modalities: phonemic (PVF), semantic (SVF) and unconstrained (UVF). We evaluated type of cluster, mean cluster size, and quantity of clusters, intersections, and returns. A total of 260 healthy subjects were assessed.Methods:Participants were divided into three age groups: young adults (18 to 39 years), middle-aged adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 32 publications
(41 reference statements)
3
31
0
4
Order By: Relevance
“…SF tasks consisted of generating words for two different categories (animals and clothes) during one minute for each category, while the PF task asked participants to say as many words as possible during one minute using the phoneme /p/. Clustering and switching analyses Clustering and switching analyses were conducted according to the methods proposed by Troyer 32 and Abwender et al, 33 Gonçalves et al's guidelines, 34 and Hermes-Pereira et al 6 We considered clusters as groups of two or more words belonging to the same category, which could be phonemic, semantic (taxonomic or thematic), or mixed (phonemic and semantic). The criteria for grouping each type of cluster were:…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…SF tasks consisted of generating words for two different categories (animals and clothes) during one minute for each category, while the PF task asked participants to say as many words as possible during one minute using the phoneme /p/. Clustering and switching analyses Clustering and switching analyses were conducted according to the methods proposed by Troyer 32 and Abwender et al, 33 Gonçalves et al's guidelines, 34 and Hermes-Pereira et al 6 We considered clusters as groups of two or more words belonging to the same category, which could be phonemic, semantic (taxonomic or thematic), or mixed (phonemic and semantic). The criteria for grouping each type of cluster were:…”
Section: Instrumentsmentioning
confidence: 99%
“…Returning and reapplying not only imply that the individual has to remember previously uttered words, thus having to use episodic and working memory capacity, but also demand attention and cognitive flexibility to keep producing words within the same category. 6 Some authors have argued that SF tends to be more sensitive for AD diagnosis compared to PF. [7][8][9] This assumption could result from the fact that the neural correlates that underlie semantic processing are usually associated with degraded areas found in AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to performance on verbal fluency tests according to the Brazilian typical aging process, studies conducted in the South and Southeast regions of the country have shown mixed results. Some authors have reported better performance among younger individuals compared to older adults for number of words produced (3,5) , whereas other studies found no significant differences between age groups (1,4,6) .…”
Section: Introductionmentioning
confidence: 92%
“…The verbal fluency test has been widely used to determine whether changes in language-cognitive profile occur during the process of normal aging (1)(2)(3)(4)(5) . In Brazil, the older population aged >65 years is growing rapidly, demographic data demonstrate a significant increase in life expectancy associated with a decrease in birth rate (6) .…”
Section: Introductionmentioning
confidence: 99%